Assessment of e-puskesmas utilization at kuranji public health center padang using the delone & mclean model - Mardi, Yuli; Oktavia, Dewi (Institute of Computer Science (IOCS), 2024)
To improve the efficiency of health service operations, the Padang City Government adopted the E-Puskesmas service system through the Kuranji public health center. In accordance with Ministry of Health standards that integrate public health center information systems, the E-Puskesmas system is a web-based public health center management application that seeks to support the delivery of health services, including patient registration, poly-level services to the health department level, and online and integrated reporting. This study serves as a measure of how well the E-Puskesmas application is used. Six evaluation variables make up the DeLone and McLean method: usage, user satisfaction, system quality, information quality, and net benefits. To measure how well the E-Puskesmas works in improving the performance of the staff of Kuranji Health Center in Padang City, the DeLone and McLean approach will be used as a model. It is expected that this model will allow the identification of elements that facilitate or hinder the use of E-Puskesmas, thus becoming a valuable tool for future evaluation and improvement. All independent variables affect the dependent variable and provide positive benefits for the health center. However, some challenges remain in the implementation of E-Puskesmas, including unstable internet connectivity and access rights for using E-Puskesmas